The just so stories - Robinette, Joseph; Kipling, Rudyard, 1865-1936. (Woodstock, Ill. : Dramatic Pub., 2001)
A play based on Rudyard Kipling's "Just So Stories," which offer humorous explanations for why animals such as elephants, camels, and giraffes look the way they do.
Cover title: Rudyard Kipling's the just so stories.
4.5
3-6
Keywords: Animals -- Juvenile drama; Children's plays; Animals -- Drama; Plays; Animals -- Drama; One act plays